The Influence of Capital Expenditures on Maintenance Expenditures in Regency or City Governments in West Sumatra Province - M. Rizky Mahaputra; M. Ridho Mahaputra (Journal of Accounting and Finance Management, 2023)
The research objective to be achieved is to provide empirical evidence that: Capital Expenditures have a significant effect on Maintenance Expenditures in the same year . Capital Expenditures have a significant effect on Maintenance Expenditures in different years. The difference in capital expenditure has a significant effect on the difference in maintenance expenditure in the same year. The type of data used in this research is secondary data. The data collection method is a documentation study method where the data collection time is in the form of a time series (time series/historical). This research uses a simple linear regression analysis method. The research results show that Capital Expenditures have a significant effect on Maintenance Expenditures in the same year, namely 2015, this is proven by a significance value of 0.000 < 0.05. Capital Expenditures have a significant effect on Maintenance Expenditures in different years. The difference in capital expenditures does not have a significant effect on the difference in maintenance expenditures in the same year, namely 2015, this is due to the significance value of 0.250 > 0.05.